Outcomes of poorly differentiated and plasmacytoid variant bladder urothelial carcinoma. Issue 1 (27th August 2021) - Lockhart, Kathleen; King, Simon; Grant, Alexander; McLeod, Nicholas; Tiu, Albert
Abstract: Objectives: The aim of this study is to assess the course and management of poorly differentiated bladder urothelial carcinoma (UC), including plasmacytoid UC (PUC), in our local area. Although bladder cancer is relatively common, PUC is a rare and aggressive subtype with a poor prognosis that is still poorly understood. Materials and Methods: A retrospective assessment of all poorly differentiated high‐grade UC over the last 15 years (2005–2020) in the Hunter New England area was completed. In total, 37 patients were included, and PUC variant was compared with the remaining poorly differentiated UC. Results: Of the included cases, eight were PUC, nine squamous variant, two neuroendocrine, and one sarcomatoid. Overall, 23 cases proceeded to cystectomy, 15 had chemotherapy (six neoadjuvant), and 11 had radiation therapy. In the PUC subgroup, three had metastatic disease at diagnosis (37.5%). Of the three PUC patients who underwent cystectomy, all were upstaged. Two PUC cases had adjuvant chemotherapy, and one case had radiation. Within the follow‐up period, the PUC group had a cause‐specific mortality of 50% with a mean survival in these patients of 202 days, compared with 37.9% cause‐specific mortality with survival of 671.55 days ( p  = 0.23) in all other undifferentiated UC cases; 5‐year cause‐specific mortality with Kaplan–Meier analysis was estimated at 26% compared with 59%, respectively ( p  = 0.058). Conclusion: Poorly differentiated UC is demonstrated to have a poor prognosis with a high mortality rate, particularly when PUC is present. Given the rarity of these variants, further studies are necessary to explore the impact of current treatment options.